Mini moveable grocery basket / Muhammad Irfan Aiman Hanapiah - Hanapiah, Muhammad Irfan Aiman (2022)
This report explains about the mini moveable grocery basket, which is a product created for the use of society. The machine will help to ease people life and reduce back injuries. The idea was found during the weekend while looking outside and saw an old lady carrying a lot of groceries. Research has been done that an old person back might get hurt due to the weight. The idea itself is to help people bring their groceries inside easily. For this project methodology, hollow steel is used for the structure of the moveable basket. A pulley system and a rope or thread that is strong enough to pull the basket when it is loaded and is used for lifting mechanism. The product is eco-friendly and easy to be used and stored. The products marketing will benefit the society, especially the elderly and the adults.